1992
DOI: 10.1111/j.1365-2222.1992.tb00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of side effects from rush‐immunotherapy with honey bee venom by pretreatment with terfenadine

Abstract: In a double-blind placebo-controlled trial on 52 patients with bee venom allergy we studied the effect of a pretreatment with terfenadine 120 mg twice daily on the occurrence of local and systemic allergic side effects from rush-immunotherapy. Large local reactions were significantly reduced by terfenadine pretreatment (P less than 0.01), while systemic side effects were observed with similar frequencies in both groups. Analysis of individual systemic allergic manifestations showed that cutaneous symptoms like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 11 publications
3
49
1
3
Order By: Relevance
“…Some studies indicated that pretreatment with antihistamine lead to a reduction in occurrence of systemic reactions following immunotherapy [52][53][54][55][56][57]. In contrast, other studies [58,59] observed no significant decrease of systemic reactions with the premedication use of antihistamines. It worth mentioning that antihistamine pretreatment does reduce systemic reactions without influencing the efficacy of immunotherapy [57].…”
mentioning
confidence: 94%
“…Some studies indicated that pretreatment with antihistamine lead to a reduction in occurrence of systemic reactions following immunotherapy [52][53][54][55][56][57]. In contrast, other studies [58,59] observed no significant decrease of systemic reactions with the premedication use of antihistamines. It worth mentioning that antihistamine pretreatment does reduce systemic reactions without influencing the efficacy of immunotherapy [57].…”
mentioning
confidence: 94%
“…[65][66][67][68] In detail, it was reported that levocetirizine decreased the rate of SSR 68 and fexofenadine decreased the rate of LLR and cutaneous SSR 67 (Table 3). Importantly, effectiveness of VIT was not negatively influenced.…”
Section: Preventive Pretreatmentmentioning
confidence: 99%
“…The H1-RA disadvantage in clinical effectiveness may be explained on the one hand by a slightly lower clinical potential of desloratadine and its predecessor loratadine in comparison to other newer antihistamines. On the other hand, previous reports dealing with premedication in SIT of which one employed loratadine [11] and the others other H1-RAs [7,8,9,10, 12, 13] were mostly designed to study the prevention of anaphylactic reactions as primary outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk-benefit ratios of conventional and rush SIT are excellent [6], side effects in these usually young and otherwise healthy patients have always been a matter of concern. Premedication with antihistamines (H1-RA) prior to each vaccination has been shown to significantly decrease the low rate of severe anaphylactic or other systemic side effects in SIT with venom as well as pollen allergens [7,8,9,10,11,12,13]. However, local reactions (LRs) are common in SIT and can reduce the patient’s compliance to this sometimes lifelong therapy [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation